The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1007/s12272-017-0997-8
|View full text |Cite
|
Sign up to set email alerts
|

Protein tyrosine phosphatase 1B inhibitors from natural sources

Abstract: Since PTP1B enzyme was discovered in 1988, it has captured the research community's attention. This landmark discovery has stimulated numerous research studies on a variety of human diseases, including cancer, inflammation, and diabetes. Tremendous progress has been made in finding PTP1B inhibitors and exploring PTP1B regulatory mechanisms. This review investigates for the natural PTP1B inhibitors, and focuses on the common characteristics of the discovered structures and structure-activity relationships. To f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 195 publications
0
34
0
Order By: Relevance
“…PTP1B is a negative regulator of insulin signaling via dephosphorylation of the insulin receptor tyrosine residues and downstream substrates to reduce the role of insulin [ 62 ]. It is well accepted that this enzyme is a promising target for hypoglycemic agent discovery, and a recent review deals with PTP1B inhibitors from natural sources [ 63 ]. In the past decade, several BPs with hypoglycemic activity targeting PTB1B have been discovered.…”
Section: Bioactivities Of Bps and Potential Use In Medicinementioning
confidence: 99%
“…PTP1B is a negative regulator of insulin signaling via dephosphorylation of the insulin receptor tyrosine residues and downstream substrates to reduce the role of insulin [ 62 ]. It is well accepted that this enzyme is a promising target for hypoglycemic agent discovery, and a recent review deals with PTP1B inhibitors from natural sources [ 63 ]. In the past decade, several BPs with hypoglycemic activity targeting PTB1B have been discovered.…”
Section: Bioactivities Of Bps and Potential Use In Medicinementioning
confidence: 99%
“…In addition, a methine proton at δ H 5.88 (1H, m, H-11) exhibited long-range correlations with carbon signals at δ C 77.6 (C-8), 49.8 (C-10), 48.4 (C-13), and 166.3 (C-7 ), indicating the second benzoyl group located at C-11. All the above data revealed that compound 1 was a pimarane-type diterpene [9,[29][30][31] and was identical with siphonol A, except only for a lack of an acetyl moiety at C-7. The downfield chemical shift of methine proton H-7 (δ H 5.51 ppm) in siphonol A [13] is quite different from the upfield chemical shift of methine proton H-7 (δ H 4.32 ppm) in 1.…”
Section: Structure Elucidationmentioning
confidence: 90%
“…There are many PTP1B inhibitors from medicinal plants. Up to now, around 56 families of genera from the natural source were found to inhibit PTP1B activity [9]. Among them, some plants and their secondary metabolites are derived from desert and steppe in the Middle East, such as Artemisia judaica, Centaurium erythraea, Achillea santolina, Capparis spinosa, Moringa peregrina, Retama raetam, Terminalia chebula, and Ziziphus spina-christi [10].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is urgent to identify potent and selective small-molecular PTP1B inhibitors. Natural products, including fatty acids, phenolics, terpenoids, steroids and alkaloids, provide a great amount of PTP1B inhibitors with structural diversity [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%